Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acsaem.2c03251
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating α-Al2O3 Nanodots into Expanded Graphite Anodes toward Stable Fast Charging for Lithium-Ion Batteries

Abstract: High-power lithium-ion batteries place high demands on the fast charging ability of electrode materials, while for the current graphite anode, it suffers from anisotropic and sluggish Li+ transport due to its small interlayer spacing. In addition, the large polarization at low lithiation potential at a high rate leads to Li+ deposition and side reactions of Li with the electrolyte. In this work, α-Al2O3 nanodots incorporated into aggregates of thin-layer graphite have been developed by facile high-energy ball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…11 Various strategies have been researched, including chemical oxidation, surface coating treatment, and porous-structure design. [12][13][14][15][16][17][18][19] By coating an arti-cial Li + conductor on the graphite surface, the interface Li + diffusion resistance could be obviously decreased, resulting in an enhanced kinetic character. 20 Lee et al applied Li 4 Ti 5 O 12 (LTO) as a coating layer for MCMB (middle phase carbon microsphere) surface modication, achieving smaller interface resistance than that of the original MCMB aer 40 cycles, due to the LTO layer inhibiting the successive decomposition of electrolyte at the electrode/electrolyte interface during long cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Various strategies have been researched, including chemical oxidation, surface coating treatment, and porous-structure design. [12][13][14][15][16][17][18][19] By coating an arti-cial Li + conductor on the graphite surface, the interface Li + diffusion resistance could be obviously decreased, resulting in an enhanced kinetic character. 20 Lee et al applied Li 4 Ti 5 O 12 (LTO) as a coating layer for MCMB (middle phase carbon microsphere) surface modication, achieving smaller interface resistance than that of the original MCMB aer 40 cycles, due to the LTO layer inhibiting the successive decomposition of electrolyte at the electrode/electrolyte interface during long cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the reversible capacities of GLG at 1, 5 and 10C were about 220, 150 and 100 mA h g −1 , respectively, which were much higher than those of the original graphite. Ma et al 13 synthesized graphite/Al 2 O 3 composites via facile high-energy ball milling. The ball milling treatment not only introduced porous structures for Li + adsorption but also expanded the layer spacing for fast Li + diffusion in the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the abovementioned problems, a large number of research works have been carrying out. At present, common modification methods mainly include mild expansion of oxidation, metal or metal oxide deposition, carbon coating, , and doping with other noncarbon elements. Among them, mild expansion of oxidation is a relatively simple and low-cost technology route to modify MG.…”
Section: Introductionmentioning
confidence: 99%
“…S8 †), suggesting the superior pseudocapacitive lithium storage of S-LLOs, in comparison to LLOs. 77 Both the enhanced diffusion kinetic coefficient and superior pseudocapacitive lithium storage facilitate the electrochemical performance of S-LLOs cathode material.…”
mentioning
confidence: 99%